Investigating Aerobic Hive Microflora: Role of Surface Microbiome of Apis Mellifera - Grigory Kashchenko; Amir Taldaev; Leonid Adonin; Daniil Smutin (Biology)
This study investigated the surface microbiome of the honeybee (Apis mellifera), focusing on the diversity and functional roles of its associated microbial communities. While the significance of the microbiome to insect health and behavior is increasingly recognized, research on invertebrate surface microbiota lags behind that of vertebrates. A combined metagenomic and cultivation-based approach was employed to characterize the bacterial communities inhabiting the honeybee exoskeleton. Our findings reveal a complex and diverse microbiota exhibiting significant spatial and environmental heterogeneity. The identification of antimicrobial compound producers, validated through both culture and metagenomic analyses, including potentially novel Actinobacteria species, underscores the potential impact of these microbial communities on honeybee health, behavior, and hive dynamics. This research contributes to a more profound ecological understanding of the honeybee microbiome, particularly in its winter configuration.